Acid base changes in arterial and central venous blood during cardiopulmonary resuscitation. Issue 2 (June 1992) - Steedman, D J; Robertson, C E
Abstract : Twenty-seven patients in cardiopulmonary arrest had simultaneous measurements of arterial and central venous blood gases during cardiopulmonary resuscitation (CPR) with a pneumatic chest comparison and ventilation device. Mean central venous and arterial hydrogen ion concentrations, PCO2 and calculated bicarbonate concentrations were significantly different (P less than 0.01) at all sampling times (0, 10 and 20 min). Central venous blood samples predominantly showed a respiratory acidosis in contrast to a mixed disturbance in arterial samples inclined towards a metabolic acidosis. The mean difference between central venous PCO2 (pcv CO2) and arterial PCO2 (pa CO2) ranged from 5.18 to 5.83 kPa reflecting the low blood flow in patients undergoing CPR. Measurement of arterial Po2 indicated adequate oxygenation using the pneumatic device. Arterial blood gas analysis alone does not reflect tissue acid base status. Bicarbonate administration during CPR may have adverse effects and any decision as to its use should be based on central venous blood gas estimations.